New Invertebrate Vectors for PST, Spirolides and Okadaic Acid in the North Atlantic - Silva, Marisa; Barreiro, Aldo; Rodríguez Villamayor, Paula; Otero Fuertes, María Paz; Azevedo, Joana; Alfonso Rancaño, María Amparo; Botana López, Luis Miguel; Vasconcelos, Vitor (Marine Drugs)
The prevalence of poisoning events due to harmful algal blooms (HABs) has declined during the last two decades through monitoring programs and legislation, implemented mainly for bivalves. However, new toxin vectors and emergent toxins pose a challenge to public health. Several locations on the Portuguese coast were surveyed between 2009 and 2010 for three distinct biotoxin groups [saxitoxin (PST), spirolide (SPX) and okadaic acid (OA)], in 14 benthic species of mollusks and echinoderms. Our main goals were to detect new vectors and unravel the seasonal and geographical patterns of these toxins. PSTs were analyzed by the Lawrence method, SPXs by LC-MS/MS, and OA by LC-MS/MS and UPLC-MS/MS. We report 16 new vectors for these toxins in the North Atlantic. There were differences in toxin contents among species, but no significant geographical or seasonal patterns were found. Our results suggest that legislation should be adjusted to extend the monitoring of marine toxins to a wider range of species besides edible bivalves This work was partially funded by the Project MARBIOTECH (reference NORTE-07-0124-FEDER-000047) within the SR & TD Integrated Program MARVALOR—Building research and innovation capacity for improved management and valorization of marine resources, supported by the Programa Operacional Regional do Norte (ON.2–O Novo Norte) and by the European Regional Development Fund, by the INTERREG IV projects Atlantox, Pharmatlantic, FCT project PesT-C/MAR/LA0015/2011, UP through IJUP projects and FEDER cofunded-grant: From Ministerio de Ciencia y Tecnología, Spain: AGL2012-40485-CO2-01. MS acknowledges FCT, FSE and MCTES for co-funding SFRH/BD/73269/2010, Vitor Ramos, João Paulo Machado and Jonathan Wilson SI